The current situation of flash flood hazard in Tay Nguyen region - Tuc, Nguyen Dang; Pha, Phan Dong; Huyen, Nguyen Xuan (Vietnam Journal of Earth Sciences, 2015)
The flash floods  are considered as one of dangerous geological hazards of the Tay Nguyen region. Though the real impacts have been appraised in recent years, the flash floods have been increasing in number, distribution range and damages. In recent years, flash floods primarily occur in mountainous areas in the provinces of Kon Tum, Dak Lak and Lam Dong. The phenomenon flash floods usually occur on the flows of level 1, 2 and 3, or even of 4, 5 and in case there were higher than the popular levels, then  should be considered as regular floodings. The flash floods normally occur at the end of the annual rainy season (September-October) usually by heavy rains. Besides, in recent years, the phenomenon of flash floods occur caused by malfunction of dam breaking or by floods discharge at a hydropower-irrigation during the rainy season were becoming the  matter of concerning. The main causes of the flash floods phenomenon in the Tay Nguyen region comprise of heavy rainfall, high slope and length of stream, high level of landslide in the basin, high slope of basin and wire catchments area are.ReferencesCao Đăng Dư, Lê Bắc Huỳnh, 2000: Lũ quét, nguyên nhân và biện pháp phòng tránh (tập I và II). Nxb. Nông nghiệp, Hà Nội. Nguyễn Xuân Huyên, Doãn Đình Lâm, Phạm Văn Hùng, Nguyễn Đăng Túc, Phan Đông Pha, 2013: Hiện trạng một số tai biến địa chất điển hình khu vực Tây Nguyên. Tạp chí Khoa học & Công nghệ Việt Nam, số 17 năm 2013 (660), 24-28, Hà Nội. Ngô Quang Toàn (chủ biên), 2000: Thuyết minh bản đồ vỏ phong hóa và trầm tích Đệ tứ Việt Nam, tỷ lệ 1/1.000.000. Cục Địa chất và Khoáng sản Việt Nam, Hà Nội. Nguyễn Trọng Yêm, Lê Thị Nghinh, Doãn Đình Lâm, Đào Thị Miên, Nguyễn Xuân Huyên, Phan Đông Pha, 1999: Flash floods in Northwest Vietnam. Geology, Series B, N.13- 14, 233-240, Hanoi. Cục Địa chất và Khoáng sản Việt Nam: Bộ bản đồ địa chất và khoáng sản tỉ lệ 1/200.000: Tờ Kon Tum (C-49-VII), tờ Đà Lạt - Cam Ranh (C-49-I và C-49-II), tờ Măng Đen - Bồng Sơn (D-49-XIII & D-49-XIV), tờ Qui Nhơn (D-49-XX), tờ Buôn Ma Thuột (D-49-XV), tờ An Khê (D-49-XIX), tờ Pleiku (D-48-XXIV), tờ Bản Đôn (D-48-XXX) đã được hiệu đính, kèm theo bản thuyết minh. Cục Địa chất và Khoáng sản Việt Nam, Hà Nội. Đài Khí tượng thủy văn Tây Nguyên. Số liệu thống kê từ năm 1983 đến năm 2012, Pleiku. Seko A.I., 1980: Quy luật hình thành và dự báo lũ bùn đá, 1980. Nxb. “Nedra”, Moskva (tiếng Nga).